To possibility of usage of FMW plasma heating scenarios in the ICR frequency range in the torsatron reactor - Longinov, A.V. (Вопросы атомной науки и техники, 2007)
The problem of fast wave plasma heating in reactor-torsatron at the ICRF range in scenarios, optimal for fusion reactor, is numerically studied. Чисельно досліджена проблема використання ВЧ-методів нагрівання плазми в області ІЦР в торсатроні-реакторі в сценаріях, оптимальних для термоядерного реактора. Численно исследована проблема использования ВЧ-методов нагрева плазмы в области ИЦР в торсатроне-реакторе в сценариях, оптимальных для термоядерного реактора.